The Boehringer Ingelheim employee study (Part 2): 10-year cardiovascular diseases risk estimation. (7th July 2016) - Kempf, K.; Martin, S.; Döhring, C.; Dugi, K.; Haastert, B.; Schneider, M.
Abstract: Background: Cardiovascular disease (CVD) may cause an economic burden to companies, but CVD risk estimations specific to working populations are lacking. Aims: To estimate the 10-year CVD risk in the Boehringer Ingelheim (BI) employee cohort and analyse the potential effect of hypothetical risk reduction interventions. Methods: We estimated CVD risk using the Framingham (FRS), PROCAM (PRS) and Reynolds (RRS) risk scores, using cross-sectional baseline data on BI Pharma employees collected from 2005 to 2011. Results were compared using Fisher's exact and Wilcoxon tests. The predictive ability of the score estimates was assessed using receiver-operating characteristics analyses. Results: Among the 4005 study subjects, we estimated 10-year CVD risks of 35% (FRS), 9% (PRS) and 6% (RRS) for men and 10% (FRS), 4% (PRS) and 1% (RRS) for women. One hundred and thirty-four (6%) men and 111 (6%) women employees had current CVD. The best predictors of prevalent CVD were the FRS and the RRS for men [area-under-the-curve 0.62 (0.57–0.67) for both]. A hypothetical intervention that would improve systolic blood pressure, HbA1c (for diabetes), C-reactive protein, triglycerides and total and high-density lipoprotein cholesterol by 10% each would potentially reduce expected CVD cases by 36–41% in men and 30–45% in women, and if smoking cessation is incorporated, by 39–45% and 30–55%, respectively, depending on the pre-intervention risk score. Conclusions: There was a substantial risk of developing CVD in this working cohort. Occupational health programmes with lifestyle interventions for high-risk individuals may be an effective risk reduction measure.